Phenolic Acid Patterns in Different Plant Species of Families Asteraceae and Lamiaceae: Possible Phylogenetic Relationships and Potential Molecular Markers - Oksana Sytar; Marek Zivcak; Kiessoun Konate; Marian Brestic (Journal of Chemistry)
Nowadays, investigations of some specific secondary metabolites estimated near 10,000 various compounds of phenolic nature in different plant species. The interest in natural compounds is not only due to their antioxidant potential, but also to their economic impact, as most of them may be extracted from underexploited plant species. The presented research work presents an extended analysis of the most important phenolic acids of the selected known and underexploited plant species from the families Asteraceae and Rosaceae with the development of phylogenic tree analysis according to the nonparametric rate smoothing (NPRS) methods. HPLC-UV analysis revealed the original spectrum of phenolic acids in selected known and underexploited plant species of the families Rosaceae and Asteraceae. The analysis of phenolic acid’s contribution from their total amount in the methanolic extract in Asteraceae found the high percentage of syringic acid in leaves varied between 64.13% and 95.13%. The detected high contribution of syringic acid among estimated phenolic acids in Asteraceae leaves suggests its possible prevalence in the representatives of the family Asteraceae. The content of draconic acid in the leaves of most representatives of the family Rosaceae which represented more than 30% of total phenolic acid content. The high presence of such phenolic acids may relate to the antioxidant activity of the studied herbal extracts.